Improved design of a multi-stage continuous-resistance trim for minimum energy loss in control valves. (1st May 2019) - Asim, Taimoor; Oliveira, Antonio; Charlton, Matthew; Mishra, Rakesh
Abstract: Control valves used in energy systems are often integrated with trims having well designed flow paths to regulate fluid flow. These trims, known as multi-stage continuous-resistance trims, comprise of staggered arrangement of circular cylinders enabling pressure drop reduction in controlled stages. The trim design process currently used doesn't ensure good local flow characteristics and relies almost entirely on the global performance indicators. The existing design largely ignores the effects of geometrical features of the trim, resulting in severe performance issues locally. In the present investigation, unique geometry-dependant local flow parameters have been analysed, using Computational Fluid Dynamics, and integrated with the global performance indicators to develop an improved trim design. Novel geometry and flow based parameters have been developed that uniquely relate the local flow behaviour within the trims to their corresponding geometrical parameters. It has been observed that the change in geometrical parameters of the trim significantly affects trim's performance, for example, reduction in the cylinders' dimensions, under same operating conditions, reduces the normalised pressure drop, flow velocity and energy by 28.4%, 26.8% and 37.9% respectively. The work highlights the need for modification in existing trim design methodology. Highlights: To critically analyse the local flow behaviour within a continuous-resistance trim. Development of novel parameters to quantify local and global flow characteristics. Effect of geometrical features of the trim on local and global performance indicators. Development of a novel parameter representing the geometrical features of the trim. Development of an improved trim design for enhanced energy performance.